Davvi Šuvva 1979 : being Sámi, becoming indigenous : vocal and musical manifestation of Sámi and indigenous movement - Angell, Synnøve (Universitetet i Tromsø, 2009)
This thesis focuses on the significance of Sámi and indigenous vocal and musical expression in ethno and indigenous political mobilizing in the 1970s and particularly in June 1979. My point of departure is the Davvi Šuvva festival; the first Sámi and international indigenous culture and music festival after the establishing of the World Council of Indigenous Peoples. It took place on a hill in a Sámi and Swedish/Finnish border village in the north of Sweden and in the middle of Sápmi. My research is based on the interviews with people who organized the festival, artists and audience as well as written contemporary sources, a film about the event and 16 authentic tapes of recordings of the concerts at Davvi Šuvva. The oral sources of eye and ear witnesses represent insider views and experiences and the contemporary written sources of attending news paper journalists and writers from other magazines represent both insider and outsider perspective. “Davvi Šuvva 1979” also documents the ethno political background of the festival and discusses various perspectives on collective identity. While powwow dance and traditional native chanting expressed First Nation and Cree Indian identity and Inuit identity was expressed by traditional drum dance and drum singing Davvi Šuvva also demonstrated how yoik conveyed various Sámi identities. My intention is to show how and why vocal and musical expressions had, and still have, a particular significance in oral indigenous cultures as a means of struggle. The conclusions reached are that manifestations of Sámi and indigenous cultural expression and resistance like the Davvi Šuvva festival contributed to pride, recovery, dignity and positive self awareness and that the festival as such strengthened Sámi identity and indigenous togetherness and belonging.